Exploratory sequential design for creation of the Miao’s traditional patterns mobile application - Shubei Qiao; Yerbol Abdramanov (Culture & History Digital Journal)
This study aimed to define a data set for the design of an app that would show Miao’s traditional patterns. At the preliminary stage, the study traced the socio-cultural transformation that the Miao people went through, and which was reflected in their traditional patterns. In the first stage of the study, an Internet survey was conducted on the international tourism platform among the population of all continents. The survey confirmed the existence of a public request for content related to Miao’s traditional patterns. The survey also determined the required information sources and approaches to training. Further, the desired content was prepared and coordinated with the help of experts in the field of Miao cultural heritage. At the final stage, usability, design, and content issues for the future mobile application were discussed during an interview with experts in the field of digital representation of artefacts.